The sexual orientation wage gap in the USA. Issue 12 (4th December 2017) - Sayers, Rachel; Levendis, John; Dicle, Mehmet
Abstract : Purpose: The purpose of this paper is to determine the nature of the wage gap between genders and sexual orientation. Design/methodology/approach: The paper uses OLS on pooled repeated cross-sections. Findings: The differences in wages between gay/straight men and women mirror what would be expected from labor force attachment more so than direct heterosexism. Research limitations/implications: The authors use a functional definition of sexual preference that reflects whether the respondent had sex with someone of the same gender in the same year. It does not ask whether the person identifies publicly as gay/lesbian/bisexual. Originality/value: The authors verify and extend earlier findings on the sexual orientation and gendered wage gap.